INFLUENCE OF STRATEGIC DIRECTION ON THE PERFORMANCE OF FINTECH FIRMS IN NAIROBI CITY COUNTY, KENYA - Naburuki, Sophie Jeruto; Kiplagat, Nehemiah; Kipchumba, Simon (European Journal of Management and Marketing Studies, 2024)
This study investigated the influence of strategic direction on the performance of financial technology (FINTECH) firms in Nairobi City County, Kenya. The research was grounded in strategic leadership theory and employed a predictive research design. The target population consisted of 154 senior and middle-level managers from 22 FINTECH firms, with a sample size of 111 respondents determined using the Taro Yamane formula. Data was collected using structured questionnaires, achieving a response rate of 82.88%. Descriptive statistics revealed that firms excel in adapting strategic direction to changing circumstances (M = 4.80, SD = 0.399) and establishing clear strategic direction (M = 4.43, SD = 0.731), but face challenges in setting clear and measurable goals (M = 1.18, SD = 0.390). In the inferential analysis, multiple linear regression revealed that strategic direction has a statistically significant positive influence on FINTECH firm performance (β = 0.890, t = 11.797, p < .05). The coefficient of determination (R² = 0.685) indicated that 68.5% of the variance in organizational performance could be explained by the strategic factors studied. The study concludes that effective strategic direction is fundamental to FINTECH firm success in Kenya's dynamic financial technology sector, validating the theoretical frameworks that emphasize strategic leadership's role in organizational performance. The research recommends that FINTECH firms implement comprehensive i Correspondence: email s_naburuki@kabarak.ac.ke Sophie Jeruto Naburuki, Nehemiah Kiplagat, Simon Kipchumba INFLUENCE OF STRATEGIC DIRECTION ON THE PERFORMANCE OF FINTECH FIRMS IN NAIROBI CITY COUNTY, KENYA European Journal of Management and Marketing Studies - Volume 9 │ Issue 2 │ 2024 155 strategic management frameworks that balance structured goal-setting processes with adaptive capabilities, while regulatory bodies develop supportive policies that encourage strategic innovation while maintaining industry stability. This research contributes to both the theoretical understanding of strategic management in the FINTECH sector and provides practical insights for industry leaders navigating complex market conditions.
Keywords: strategic direction, FINTECH, organizational performance, strategic leadership theory